Answer:
1. [tex]\dfrac{44}{13}=3\dfrac{5}{13}[/tex]
2. 9.6
3. 0
Step-by-step explanation:
Thales’ Theorem: If arms of an angle are cut by parallel straight lines, then the ratio of the lengths of the line segments obtained on one arm are equal to the corresponding segments obtained on the second arm.
1. By Thales's theorem,
[tex]\dfrac{9}{4}=\dfrac{11-x}{x}\\ \\9x=4(11-x)\ [\text{Cross multiply}]\\ \\9x=44-4x\\ \\9x+4x=44\\ \\13x=44\\ \\x=\dfrac{44}{13}[/tex]
2. By Thales's theorem,
[tex]\dfrac{8}{12}=\dfrac{x}{24-x}\\ \\12x=8(24-x)\ [\text{Cross multiply}]\\ \\12x=192-8x\\ \\12x+8x=192\\ \\20x=192\\ \\x=9.6[/tex]
3. By Thales's theorem,
[tex]\dfrac{4x}{5x}=\dfrac{4x-8}{6x-10}\\ \\\dfrac{4}{5}=\dfrac{4x-8}{6x-10}\\ \\5(4x-8)=4(6x-10)\ [\text{Cross multiply}]\\ \\20x-40=24x-40\\ \\20x=24x\\ \\4x=0\\ \\x=0[/tex]
When Maggie hooks her dog up to a rope that is staked in the yard, the dog can walk a distance of about 76 feet along the circumference. To the nearest tenth, what is the length of the rope?
C = 76 ft
Choices
12.1 ft
24.2 ft
12.7 ft
8.1 ft
Answer:
12.1
Step-by-step explanation:
76/2π
= 38/π
= 12
Answer: 12.1 ft
Step-by-step explanation:
Hi, to answer this we have to apply the circumference formula:
C= 2πr
Where:
C = circumference ( in this case is 76, since the dog can walk a distance of about 76 feet along the circumference.)
r = radius. (In this case the radius is the length of the rope, because the stake is in the center of the circumference)
Replacing with the values given and solving for "r":
76 = 2πr
76 /( 2π)= 12.0957= 12.1 ft
The perimeter of a square room is 80 feet. The area of the room is how many square feet?
Answer:
400
Step-by-step explanation:
What’s the slope of (-2,1) and (3,-3)
Answer:
-4/5
Step-by-step explanation:
slope = m = (difference in y)/(difference in x) = (-3 - 1)/(3 - (-2)) =-4/5
Substitution Problem:
x+5y=4
3x+15y=-1
There are no solution of System of equations
We have to given that,
System of equations are,
x+5y=4
3x+15y=-1
Now, We can use substitution method as,
x+5y=4 .(i)
3x+15y=-1 .. (ii)
From (i);
x = 4 - 5y
Put above value in (ii);
3 (4 - 5y) + 15y = - 1
12 - 15y + 15y = - 1
12 = - 1
Which is not possible.
Hence, There are no solution of System of equations
Learn more about systems of equations at:
brainly.com/question/14323743
#SPJ6
Need help with this math problem
In the figure, Blueline is Line AB and Redline is target line.
You can see that the target line does not pass through (18,-8)
Step-by-step explanation:
In the figure, Blueline is Line AB and Redline is target line.
You can see that the target line does not pass through (18,-8)
Taking a bottom-left corner of the graph as (0,0)
Given Line AB,
Point A is located as (4,9)
Point B is located as (16,1)
The slope of AB is
[tex]=\frac{Y1-Y2}{X1-X2}[/tex]
[tex]=\frac{9-1}{4-16}[/tex]
[tex]=\frac{8}{-12}[/tex]
[tex]=\frac{-2}{3}[/tex]
The question says " Draw a line passes through C(13,12) and parallel to Line AB "
Now, Let the equation of the target line is y=mx + c
Where m=slope and c is the y-intercept
The target line is parallel to the line AB
The slope of the Target line = The slope of the Line AB [tex]=\frac{-2}{3}[/tex]
m=[tex]=\frac{-2}{3}[/tex]
We can write, the equation of the target line is
[tex]y=\frac{-2}{3}x + c[/tex]
Also, the Target line is passing through C(13,12)
Point C satisfies the equation
[tex]y=\frac{-2}{3}x + c[/tex]
[tex]12=\frac{-2}{3}13 + c[/tex]
[tex]12=\frac{-26}{3} + c[/tex]
[tex]12+\frac{26}{3}=c[/tex]
[tex]c= 12+\frac{26}{3}[/tex]
[tex]c= \frac{62}{3}[/tex]
Replacing the value
the equation of the target line is
[tex]y=\frac{-2}{3}x + c[/tex]
[tex]y=\frac{-2}{3}x + \frac{62}{3} [/tex]
[tex]3y= -2x + 62 [/tex]
It is also asked that if a line is extended , would it passes through the (18,-8)?
If a line passes through the point (18-,8) then, that point must satisfy the equation of a line
the equation of the target line is [tex]3y= -2x + 62 [/tex]
[tex]3(-8)= -2(18) + 62 [/tex]
[tex](-24)= (-36) + 62 [/tex]
[tex](-24)= (-36) + 62 [/tex]
[tex](-24)= 26 [/tex]
Left land side is not equal to right hand side.
Therefore. a line does not pass through the point (18,-8)
What's 4 3×7 + 2 1×3
Answer: 90
Step-by-step explanation: You equation is 4(3*7) + 2(1*3). To solve this, you first solve what is on the inside of the parenthesis. so 3 times 7 is 21. And 1 times 3 is 3. So now your equation looks like this 4(21) + 2(3). 4 times 21 is 84 and 2 times 3 is 6. So now your equation is 84 + 6 which equals 90.
Answer:
90
Step-by-step explanation:
4(3*7)+2(1*3)=4(21)+2(3)=84+6=90
A boat goes 50 km downstream in the same time that it takes to go 30 km upstream. The speed of the stream is 3km/hour. Find the speed of the boat in still water.
Answer:
12 km/h
Step-by-step explanation:
Given: Distance covered by boat downstream = 50 km
Distance covered by boat upstream = 30 km
Time taken by boat in down stream and upstream are equal.
Speed of the stream = 3 km/h
Let x be the speed of boat in still water.
∴ Speed of boat in downstream [tex](s_1)[/tex] = [tex](x+3)\ km/h[/tex]
Speed of boat in upstream [tex](s_2)[/tex] = [tex](x-3)\ km/h[/tex]
As we know, [tex]Time = \frac{Distance}{speed}[/tex]
And time remain same for both upstream and downstream
∴ [tex]\frac{50}{(x+3)} = \frac{30}{(x-3)}[/tex]
Now, cross multiply both side
⇒ [tex]50\times (x-3) = 30\times (x+3)[/tex]
⇒ [tex]50x-30x = 150+90[/tex]
∴ [tex]x= 12\ km/h[/tex]
∴ Speed of boat in still water is 12 km/h
Simplify 5(x + 9) ................
Answer:
5(x + 9) = 5x + 45Step-by-step explanation:
Use the distributive property:
a(b + c) = ab + ac
5(x + 9) = (5)(x) + (5)(9) = 5x + 45
2. A line has a slope of which of the
following points could this line pass through?
A. (15, 13) and (0,4)
B. (3,9) and (6, 14)
C. (0,4) and (1999)
D. (5,7) and (10,10)
Answer:
B.
Step-by-step explanation:
The cost of 5 squash and 2 zucchini is $1.32. Three squash and 1 zucchini cost $0.75. Find the cost of each vegetable.
Final answer:
By solving a system of equations, we find that the cost of one squash is $0.18 and the cost of one zucchini is $0.21.
Explanation:
The question involves solving a system of linear equations to determine the cost of each vegetable. Let's define x as the cost of one squash and y as the cost of one zucchini. We have the two equations based on the information provided:
5x + 2y = $1.323x + y = $0.75We can solve this system using either substitution or elimination methods. For this example, I'll use the substitution method:
Solve the second equation for y: y = $0.75 - 3x.Substitute the expression for y in the first equation: 5x + 2($0.75 - 3x) = $1.32.Simplify and solve for x: 5x + $1.50 - 6x = $1.32, which simplifies to x = $1.50 - $1.32, so x = $0.18.Substitute x back into the equation for y: y = $0.75 - 3($0.18), so y = $0.75 - $0.54, thus y = $0.21.Therefore, the cost of one squash is $0.18 and the cost of one zucchini is $0.21.
Final answer:
To find the cost of each vegetable, a system of linear equations was set up and solved, revealing the cost of one squash to be $0.18 and the cost of one zucchini to be $0.21.
Explanation:
The cost of 5 squash and 2 zucchini is $1.32, and the cost of 3 squash and 1 zucchini is $0.75. To find the cost of each vegetable, we can set up a system of linear equations and solve for the unknowns.
Let 's' represent the cost of one squash and 'z' represent the cost of one zucchini. We can then create two equations based on the information given:
5s + 2z = $1.32
3s + 1z = $0.75
Now, we need to solve this system of equations. An effective way to do this would be using the substitution or elimination method. For simplicity, let's use the elimination method:
Multiply the second equation by 2 to align the coefficients of z:
6s + 2z = $1.50
Now subtract the modified second equation from the first:
(5s + 2z) - (6s + 2z) = $1.32 - $1.50
-s = -$0.18
s = $0.18
With the cost of one squash known, substitute 's' back into one of the original equations to find 'z':
3(0.18) + z = $0.75
0.54 + z = $0.75
z = $0.75 - $0.54
z = $0.21
So, one squash costs $0.18, and one zucchini costs $0.21.
simplify 5(6x+9) using the distributive property
Answer:
30x+45
Step-by-step explanation:
5*6x=30x
5*9=45
Answer:
30x + 45
Step-by-step explanation:
We distribute the 5 to the variable 6x and the constant 9:
5(6x+9)
5 x 6x = 30x
5 x 9 = 45
The answer is 30x + 45
What criteria can be used to prove these two triangles congruent?
A.AAS
B.ASA
C.HL
D.SSA
Answer:
AAS
Step-by-step explanation:
Section #1: Solvi
1) Find the solution to each equation.
A) 4(2x - 1) = -3x + 32
Section
1) Find the solution to each equation.
A) 4(2x - 1) = -3x + 32
Answer:The solution to the equation 4(2x - 1) = -3x + 32 is x = 3.273
Solution:Need to find the solution of following equation
4(2x - 1) = -3x + 32
Let use BODMAS rule to solve the expression
According to Bodmas rule, if an expression contains brackets ((), {}, []) we have to first solve or simplify the bracket followed by of (powers and roots etc.), then division, multiplication, addition and subtraction from left to right.
On opening the bracket of left hand side we get
[tex]4 \times 2x-4 \times 1=-3 x+32[/tex]
Now perform multiplication,
8x – 4 = -3x + 32
On bringing terms having variable x in left hand side and constant term on right hand side we get
8x + 3x = 32 + 4
=> 11x = 36
On dividing both sides by 11, we get
[tex]\begin{array}{l}{\Rightarrow \frac{11 x}{11}=\frac{36}{11}} \\\\ {\Rightarrow x=\frac{36}{11}=3.273}\end{array}[/tex]
Hence solution of equation 4(2x - 1) = -3x + 32 is 3.273
Two pipes are connected to the same tank. When working together., they can fill the tank in 10hrs. The larger pipe, working alone, can fill the tank in 15 hrs less time than the smaller one. How long would the smaller one take, working alone, to fill the tank
Answer:
30 hours
Step-by-step explanation:
Let the small pipe take time "t" to fill up the tank alone
Since larger pipe takes 15 HOURS LESS, so it will take "t - 15" time to fill up the tank alone
Let the whole tank be equal to "1" and each pipe fills up a fraction of the tank.
Smaller Pipe fills up 10/t, and
Larger Pipe fills up 10/(t-15)
Totalling "1". So we can write:
[tex]\frac{10}{t}+\frac{10}{t-15}=1[/tex]
Now, we solve for t. First, we multiply whole equation by (t)(t-15), to get:
[tex]t(t-15)*[\frac{10}{t}+\frac{10}{t-15}=1]\\(t-15)(10)+10t=t(t-15)[/tex]
Now we multiply out and get a quadratic and solve by factoring. Shown below:
[tex](t-15)(10)+10t=t(t-15)\\10t-150+10t=t^2-15t\\20t-150=t^2-15t\\t^2-35t+150=0\\(t-30)(t-5)=0\\t=5,30[/tex]
Since, this time is for the smaller pipe (which takes longer than 15 hours), so we disregard t = 5 and take t = 30 as our solution. So,
Smaller pipe takes 30 hours to fill up the tank alone
The smaller pipe takes 30 hours to fill the tank on its own, determined by solving the equation derived from the combined and individual rates at which each pipe fills the tank.
Since they can jointly fill the tank in 10 hours, we can use the rates at which they fill the tank to set up the equation: 1/x + 1/(x - 15) = 1/10. To find the solution, we multiply each term by 10x(x - 15) to clear the denominators, which gives us 10(x - 15) + 10x = x(x - 15). This simplifies to 20x - 150 = x^2 - 15x. Rearranging the terms yields x^2 - 35x + 150 = 0, which can be factored into (x - 30)(x - 5) = 0. Thus, x could be either 30 hours or 5 hours. Since x - 15 must also be positive, x = 30 hours is the correct solution, meaning the smaller pipe takes 30 hours to fill the tank alone.
Please please answer this correctly
Answer:
63 Inches.
Step-by-step explanation:
2 yards - 9 inches is equal to 1.75 yards and when converted to inches, equals 63 inches.
Answer:
63 inches
Step-by-step explanation:
2 yards - 9 inches = 1.75 yards and when converted is 63 inches
(2x^3+6x-1)+(3x^2-7x)
For this case we must simplify the following expression:
[tex](2x ^ 3 + 6x-1) + (3x ^ 2-7x)[/tex]
We eliminate the parentheses taking into account that:
[tex]+ * + = +\\+ * - = -[/tex]
So, we have:
[tex]2x ^ 3 + 6x-1 + 3x ^ 2-7x =[/tex]
We add similar terms taking into account that:
Different signs are subtracted and the sign of the major is placed:
[tex]2x ^ 3 + 3x^2-x-1[/tex]
Answer:
[tex]2x ^ 3 + 3x^2-x-1[/tex]
A manufacturing plant earned $80 per man-hour of labor when it opened. Each year, the plant earns an additional 5% per man-hour.Write a function that gives the amount A(t) that the plant earns per man-hour t years after it opens.
A function that gives the amount that the plant earns per man-hour t years after it opens is [tex]\mathrm{A}(\mathrm{t})=80 \times 1.05^{\mathrm{t}}[/tex]
Solution:Given that
A manufacturing plant earned $80 per man-hour of labor when it opened.
Each year, the plant earns an additional 5% per man-hour.
Need to write a function that gives the amount A(t) that the plant earns per man-hour t years after it opens.
Amount earned by plant when it is opened = $80 per man-hour
As it is given that each year, the plants earns an additional of 5% per man hour
So Amount earned by plant after one year = $80 + 5% of $80 = 80 ( 1 + 0.05) = (80 x 1.05)
Amount earned by plant after two years is given as:
[tex]=(80 \times 1.05)+5 \% \text { of }(80 \times 1.05)=(80 \times 1.05)(1.05)=80 \times 1.052[/tex]
Similarly Amount earned by plant after three years [tex]=80 \times 1.05^{t}[/tex]
[tex]\begin{array}{l}{\Rightarrow \text { Amount earned by plant after } t \text { years }=80 \times 1.05^{t}} \\\\ {\Rightarrow \text { Required function } \mathrm{A}(t)=80 \times 1.05^{t}}\end{array}[/tex]
Hence a function that gives the amount that the plant earns per man-hour t years after it opens is [tex]\mathrm{A}(t)=80 \times 1.05^{t}[/tex]
How do you solve : through: (1, -3) and (-5,0)?
Answer:
-1/2
Step-by-step explanation:
m=(y2-y1)/(x2-x1)
m=(0-(-3))/(-5-1)
m=(0+3)/(-6)
m=3/-6
simplify
m=-1/2
to find the product 3 3/8 * 4 1/9.tara rewrote 3 3/8 as 17/8 amd 4 1/9 as 13/9. she multiplies the fractions to find the product 221/72. what error did she make
Answer:
The error Tara made is she rewrote incorrectly 3 3/8 as 17/8 and 4 1/9 as 13/9,
the corrected number can be rewrote as 3 3/8 as 27/8 and 4 1/9 as 37/9.
Step-by-step explanation:
To find the Product of:
[tex]3\frac{3}{8}\times 4\frac{1}{9}[/tex]
The Number can be rewrote as,
[tex]\frac{3\times8+3}{8}\times \frac{4\times9+1}{9}\\\\\frac{24+3}{8}\times \frac{36+1}{9}\\\\\frac{27}{8}\times \frac{37}{9}[/tex]
Tara made error here she rewrote the number incorrectly 3 3/8 as 17/8 amd 4 1/9 as 13/9.
Now multiplying the fraction we get
[tex]\frac{999}{72}[/tex]
Because she rewrote incorrectly which led her answer to multiplication of fraction, the product too was incorrect which she wrote as 221/72.
Amy has 20 quarters.sodas cost $.75 write an expression for how many quarters Amy has left after buying D amount of sodas
The expression x=20-3D will present the amount Amy has left after buying D sodas.
Step-by-step explanation:
Given,
Total amount = 20 quarters
Cost of sodas = $0.75 = 0.75*100 = 75 cents
25 cents = 1 quarter
1 cent = [tex]\frac{1}{25}\ quarter[/tex]
75 cents = [tex]\frac{1}{25}*75[/tex] = 3 quarters
Amount of D sodas = 3D
Let x be the amount left with Amy.
Amount left = total amount - Amount of D sodas
[tex]x=20-3D[/tex]
The expression x=20-3D will present the amount Amy has left after buying D sodas.
Keywords: fractions, subtraction
Learn more about subtraction at:
brainly.com/question/2977815brainly.com/question/3071107#LearnwithBrainly
Simplify this expression and write the result using positive exponents only
Answer:
[tex]\displaystyle 5b^{-4}[/tex]
Step-by-step explanation:
[tex]\displaystyle 5b^{-4} = (-5a^4b^{-7})(-a^{-4}b^3) \\ \\ \frac{5}{b^4} = 5b^{-4}[/tex]
According to the Negative Exponential Rule [part II], you bring the denominator to the numerator WHILE ALTERING THE INTEGER SYMBOL FROM POSITIVE TO NEGATIVE:
[tex]\displaystyle b^{-n} = \frac{1}{b^n}[/tex]
I am joyous to assist you anytime.
Brian buys 2 books for 15.99 each, a DVD for 19.95, and a magazine for 2.50 he also returns a jacket that cost 42.59.what is the net change in the amount of money he has after his shopping trip please help!!!
Answer:
Amount of money Brain has is 11.84 after his shopping trip.
Step-by-step explanation:
Given:
cost of books = 15.99 each
Cost of 2 books = [tex]15.99\times 2 = 31.98[/tex]
Cost for DVD = 19.95
Cost of Magazine = 2.50
Money he gets return back for jacket = 42.59
Solution:
We will first find the total amount used for shopping.
Total Shopping done = Cost of 2 books + Cost for DVD + Cost of Magazine = [tex]31.98+19.95+2.50= 54.43[/tex]
Now we will find the amount left after shopping which will be equal to the total amount used for shopping minus money he got in return for jacket.
Now net amount Left after shopping = Total Shopping done - Money he gets return back for jacket = [tex]54..43-42.59 =11.84[/tex]
Hence amount of money Brain has is 11.84 after his shopping trip.
Petra borrows $200 for 1 year with a simple interest rate
of 4.5%. Complete the equation that represents the total
amount that Petra has to pay after 1 year.
Amount Borrowed + Amount of Interest = Total to Pay Back
+
L
x
) =
The total amount petra has to pay after 1 year is $ 209
The equation used is: Total amount to pay back = Amount Borrowed + Amount of Interest
Solution:Given that,
Petra borrowed $ 200 for 1 year with simple interest rate 4.5 %
We are asked to find the amount that petra has to pay back after 1 year
Total to Pay Back = Amount Borrowed + Amount of Interest
Let us first calculate the amount of interest Petra has to pay for 1 year
Given that simple interest rate = 4.5%
The simple interest is given as:
[tex]\text { simple interest }=\frac{\text { principal } \times \text {rate} \text { of interest } \times \text { number of years }}{100}[/tex]
[tex]\text { simple interest }=\frac{200 \times 4.5 \times 1}{100}=2 \times 4.5=9[/tex]
Thus the amount of interest = $ 9
Total to Pay Back = Amount Borrowed + Amount of Interest
Total to Pay Back = 200 + 9 = 209
Thus the total amount petra has to pay after 1 year is $ 209
0.8 hectometers = what millimeters
Answer:
Which is equal to 0.0865 hectometers?
86.5 millimeters
865 millimeters
8,650 millimeters
86,500 millimeters
Step-by-step explanation:
an elementary school teacher wants to know if the words in a book are too difficult for her students. She reads the first sentence on the first page in every chapter and finds three words her students would not know. what is the sample in this situation
A.the three words her students would not know
B. the words that she reads that her students would know
c. every word in the book
d.every word in the first sentence of the first page of every chapter<—my answer
Answer:
d.every word in the first sentence of the first page of every chapter.
Step-by-step explanation
the sample space means the set of total possible outcomes or ALL possible outcomes.so here, the situation is about the teacher reading a sentence.the favorable outcome is the set which has all the words that the students would not know from all the words read by the teacher or simply from the sample space.since the teacher reads the first sentence on the first page in every chapter , all the words in that sentence will be sample in this situation.(2.3 x 10^3) + (6.9 x 10^3)
The solution of (2.3 x 10^3) + (6.9 x 10^3) is [tex]9.2 \times 10^3[/tex] that is 9200
Solution:Need to solve the following expression:
[tex]\left(2.3 \times 10^{3}\right)+\left(6.9 \times 10^{3}\right)[/tex]
There are two terms in given expression
Let’s find GCF for this two terms
The greatest number that is a factor of two (or more) other numbers. When we find all the factors of two or more numbers, and some factors are the same ("common"), then the largest of those common factors is the Greatest Common Factor.
[tex]\begin{array}{l}{2.3 \times 10^{3}=2.3 \times 10^{3}} \\\\ {6.9 \times 10^{3}=3 \times 2.3 \times 10^{3}}\end{array}[/tex]
[tex]\text {So GCF between two terms is } 2.3 \times 10^{3}[/tex]
Let’s bring GCF out of the bracket in expression for sake of simplicity.
[tex]\begin{array}{l}{=>2.3 \times 10^{3}(1+3)} \\\\ {=>2.3 \times 10^{3} \times 4} \\\\ {=>9.2 \times 10^{3}} \\\\ {=>9200}\end{array}[/tex]
Hence on solving the expression (2.3 x 10^3) + (6.9 x 10^3) the result we get is [tex]9.2 \times 10^3[/tex] that is 9200
(-511) + (+709) = solve.
Answer:
198
Step-by-step explanation:
-511 + (+709) =
709 - 511 = 198
Answer:
-511 + 709 = 198
Step-by-step explanation:
-511+709 is the same as 709-511
Juan is a software salesman. His base salary is $2300, and he makes an additional $90 for every copy of Math is Fun he sells.
Let P represent his total pay (in dollars), and let N represent the number of coples of Math is Fun he sells. Write an equation relating P to N. Then use this
equation to find his total pay if he sells 21 coples of Math is Fun.
Equation:
8 O=D
xs ?
Total pay if Juan sells 21 coples: s]
How do I get the answer
The equation to represent Juan's pay is P = 2300 + 90N. If he sells 21 copies of the book, his total pay would be $4190.
Explanation:Pay Calculation
Given that Juan's base salary is $2300 and he makes an additional $90 for every copy of Math is Fun he sells, we can write an equation relating P (total pay) to N (number of sales) by adding together his base pay and his earnings from selling the books. This can be written as P = 2300 + 90N. We can then use this equation to calculate Juan's total pay if he sells 21 copies of the Math is Fun book. By substituting N = 21 into our equation, we get P = 2300 + 90*21, which simplifies to P = 2300 + 1890 = $4190. So, if Juan sells 21 copies of Math is Fun, his total pay would be $4190.
Learn more about Pay Calculation here:https://brainly.com/question/809624
#SPJ3
How many solutions does this system of equations have?
exactly two
none
infinitely many
exactly one
Graph of a system of linear equations. Equation 1 is 3x plus 2y equals 6. Equation 2 is negative 4x plus 5y equals 15. The graphs intersect at a point.
Answer:
exactly oneStep-by-step explanation:
The system of linear equations have:
one solution, infinitely many solutions or no solution.
One solution if the lines intersect.
Infinitely many solutions if the lines are the same (overlap)
There is no solution if the lines are parallel (they do not have a common point).
In the graph, two lines intersect. Therefore, the system of equations has one solution (0, 3).
Whose class would you rather be in, if each teacher has different grading schemes?
Mr. Winking’s Grade Weights
Homework Average
10%
Quiz Average
25%
Test Average
45%
Final Exam Grade
20%
Ms. Sand’s Grade Weights
Homework Average
15%
Quiz Average
20%
Test Average
40%
Final Exam Grade
25%
Your Grade Report:
Homework Average: 95%
Quiz Average: 85%
Test Average: 87%
Final Exam Grade: 90%
Step 1: Find your final average for Mr. Winking’s Class (10 points)
Step 2: Find your final average for Ms. Sand’s Class. (10 points)
Step 3: Determine which class you would rather be in. Write in complete sentences. Use your answers from steps 1 and step 2 to justify your answer. (10 points)
Answer:
Mr. Winking 87.9%
Ms. Sand 88.55%
Ms. Sand's class is better
Step-by-step explanation:
Step 1: Average in Mr. Winking's Class 87.9%
Convert each weight factor to a decimal.
Homework 10% = 0.1
Quiz 25% = 0.25
Test 45% = 0.45
Exam 20% = 0.2
Multiply your grades by the weight factors:
Homework 0.1 X 95% = 9.5%
Quiz 0.25 X 85% = 21.25%
Test 0.45 X 87% = 39.15%
Exam 0.2 X 90% = 18%
Add all of these values:
9.5% + 21.25% + 39.15% + 18%
= 87.9%
Step 2: Average in Ms. Sand’s Class 88.55%
Convert each weight factor to a decimal.
Homework 15% = 0.15
Quiz 20% = 0.2
Test 40% = 0.4
Exam 25% = 0.25
Multiply the weight factors by your grades:
Homework 0.15 X 95% = 14.25
Quiz 0.2 X 85% = 17
Test 0.4 X 87% = 34.8
Exam 0.25 X 90% = 22.5
All all these values:
14.25 + 17 + 34.8 + 22.5
= 88.55%
Step 3:
I would rather be in Ms. Sand's class. My average in her class would be 88.55%, whereas in Mr.Winking's Class, my average would be 87.9%. 88.55% is a higher mark than 87.9% and I want higher marks. Therefore, I would get higher marks in Ms. Sand's class.